ВИКОРИСТАННЯ АКТИВНИХ МЕТОДІВ НАВЧАННЯ У ФОРМУВАННІ КОМУНІКАТИВНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ІНЖЕНЕРІВ-ПЕДАГОГІВ - Маляров, Олександр (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті досліджуються особливості формування комунікативної компетентності майбутніх інженерів-педагогів за допомогою активних методів навчання. Розкрито роль активних методів навчання у забезпеченні якісної навчально-пізнавальної діяльності інженерів-педагогів. Вказано на необхідність удосконалення методів навчання, їх спрямування на розвиток пізнавальної активності, самостійності та творчості студентів. Визначено найефективніші активні методи навчання, які доцільно застосовувати при формуванні комунікативної компетентності майбутніх інженерів-педагогів (тренінги, проблемні ситуації (метод кейсів), ділові ігри) та особливості їх використання у процесі навчання майбутніх інженерів-педагогів. В статье исследуются особенности формирования коммуникативной компетентности будущих инженеров-педагогов с помощью активных методов обучения. Раскрыта роль активных методов обучения в обеспечении качественного учебно-познавательной деятельности инженеров-педагогов. Указано на необходимость совершенствования методов обучения, их направленность на развитие познавательной активности, самостоятельности и творчества студентов. Определены наиболее эффективные активные методы обучения, которые целесообразно применять при формировании коммуникативной компетентности будущих инженеров-педагогов (тренинги, проблемные ситуации (метод кейсов), деловые игры) и особенности их использования в процессе обучения будущих инженеров-педагогов. The article deals with the peculiarities of communicative competence of future engineers-teachers using active learning methods. Considered the role of active learning methods to ensure quality teaching and learning of engineersteachers. Specified on the necessity of improving teaching methods, their focus on the development of cognitive activity, independence and creativity of students. Determined the most effective active learning methods that are appropriate to use in the formation of the communicative competence of future engineers-teachers (training, problem situations (method of cases), business games) and features their use in the process of teaching of future engineersteachers. It is concluded that the active methods are changing the nature of mental activities of future professionals in the teaching and learning activities, thus the process knowledge enables them to move through intellectual development. The use of active learning methods in the professional training of future engineers-teachers contribute effectively to form the communicative competence of autonomy in decision-making, enhance thinking.